2005
DOI: 10.1111/j.1399-0004.2005.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of 6q subtelomere deletions to define genotype/phenotype correlations

Abstract: Testing for subtelomere abnormalities in patients with idiopathic mental retardation has become a useful diagnostic tool. However, limited data exist regarding genotype/phenotype correlations for specific subtelomere imbalances. We have ascertained five patients with 6q subtelomere deletions either as a result of an isolated deletion or as a result of an unbalanced translocation, and developed a molecular ruler assay utilizing BAC or PAC clones and determined the size of the deleted regions to range from <0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 30 publications
(49 reference statements)
7
112
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9]15,16 Though the clinical phenotypes associated with this deletion are quite variable, reports in unrelated subjects from independent investigators have shown that ACC, PNH, polymicrogyria, hydrocephalus, and cerebellar malformations are the consistently observed features. A recent analysis of a comprehensive map of loci for ACC from 374 patients revealed that chromosome 6q27 was one of the few loci wherein six or more subjects with ACC have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9]15,16 Though the clinical phenotypes associated with this deletion are quite variable, reports in unrelated subjects from independent investigators have shown that ACC, PNH, polymicrogyria, hydrocephalus, and cerebellar malformations are the consistently observed features. A recent analysis of a comprehensive map of loci for ACC from 374 patients revealed that chromosome 6q27 was one of the few loci wherein six or more subjects with ACC have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Structural brain malformations are consistently observed in these patients and include agenesis of the corpus callosum (ACC), periventricular nodular heterotopia (PNH), polymicrogyria, hydrocephalus, and cerebellar malformations. [1][2][3][4][5][6][7][8][9][10] Whereas previous studies have attempted to delineate the critical region responsible for brain malformations in patients with terminal 6q27 deletions, the sensitivity of the methodologies used has prevented the fine-mapping of the critical region. 1,6 A detailed genomic analysis of the subtelomeric chromosome 6q region would help identify the putative genes involved in the causation of brain malformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This presents a significant diagnostic problem because patients with 6qter deletions smaller than 1.7 Mb have a clinical phenotype. 16 Finally, abnormalities involving mismapped or poorly performing clones that are proximal to the most terminal clones could be misinterpreted as noncontiguous deletions or duplications. For example, the third and fourth clones from the 7q subtelomere (RP11-324E12 and RP11-11B21, Table 2) are both mismapped, leading to confusing and potentially misleading results.…”
Section: Validation Of Array Cgh Platformsmentioning
confidence: 99%
“…Variants in TAF1 are associated with ID and microcephaly 13,14 whereas the reduction in TAF1 expression is associated with XDP 10 (Table S1). Also, in TBP, the expansion of the polyglutamine (polyQ) tract causes SCA17 probably in a gain-of-function mode, whereas heterozygous deletion of TBP is probably responsible for ID and microcephaly 9,29 (Table S1). Therefore, we also suggest that TAF13 and possibly other constituents of TFIID are multi-functional proteins whose pathogenic variants could lead to different phenotypes depending on the localization of the pathogenic variant.…”
mentioning
confidence: 99%